Aplicação do ciclo PDCA no controle de qualidade higiênico sanitário de um serviço de alimentação em uma instituição assistencial para crianças e adolescentes - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The PDCA cycle, which means plan, do, check, act, is a quality tool that can be used in the hygienic and sanitary control of food services. Verify the effectiveness of implementing PDCA cycle in the hygienic quality of a food service in a social project. The research was developed through the application of the PDCA tool. The evaluation instrument used was the checklist of legislation n. 78/2009, used in 3 different moments. Data were analyzed by frequency of conformities. In the first application it was found 38.02% of conformities, in the second 56.2% and in the third 69.42%, a total growth of 31.4%. Among them, action plans were elaborated and implemented, such as training, organization of the physical space and purchase of materials and utensils. The categories that improved the most during the study were handlers, from 23,08 % to 53,84%, exposure to prepared food consumption, from 33,33% to 50% and food preparation, from 23,53% to 41,18%. In the present study, it was concluded that the PDCA cycle was effective in improving the hygienic quality of a food service in a social project.
Application of the PDCA cycle in sanitary hygiene quality control of a food service in a care institution for children and adolescents
Keywords: Boas práticas; Melhorias continuas; Controle de qualidade; Good manipulation practices; Food services; Quality control; CNPQ::CIENCIAS DA SAUDE